LEARNING ENGLISH ON SPEAKING SUBJECT BY USING THE FAIRY TALES WITH LOCAL WISDOM FOR ELEMENTARY AND HIGH SCHOOLS’ STUDENTS - Erisa Kurniati (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2015)
This article is talking about learning English on speaking subject by using the fairy tales with local wisdom for elementary and high schools’ students. This article aims to identify and describe: first, the implementation of learning English on speaking subject by using the fairy tales with local wisdom that consist of measures of learning, teaching, learning activities, and evaluation and second, the value of local wisdom contained in the fairy tales that used in learning English on speaking subject. The implementation of learning English on speaking subject by using the fairy tales with local wisdom, using a thematic approach which consists of: the creation of attractive atmosphere with musical instruments, the process of extracting the insight students through questions and answers, the telling of fairy tales by teachers with regard domains of storytelling aspect, the telling of fairy tales by students with attention to aspects of storytelling, questions and answers in order to provoke the students to express opinions, inference, evaluation, and follow-up with clarifications and amplifications on the end of the lesson. Learning evaluation conducted by the evaluation process and the evaluation of results. In addition, this article also showed that the value of local wisdom contained in fairy tales are the moral individual, social, and religious. Key words: Learning English on Speaking Subject, Fairy Tales, Local Wisdom